X-Ray Contrast Media OVERVIEW, USE AND PHARMACEUTICAL ASPECTS - Speck, Ulrich (Springer Berlin Heidelberg, 2018)
This open access book is an overview on CT/X-ray contrast media designed for radiologists and other medical specialists who use contrast media in imaging and interventional procedures as well as related scientists on the use and pharmaceutical aspects of X-ray contrast media. The overall goal of this book is to provide a comprehensive overview relevant for the optimal use of x-ray contrast media covering next to the historic development, their structure and properties also practical information for handling of contrast media, and explanation of the relevant risks during use and measures for prevention and treatment of potential side effects. .